About Portfolio Theory Models - Saipnazarov Shaylavbek Aktamovich; Saipnazarov Sherbek Shaylavbekovich (International Journal on Economics, Finance and Sustainable Development, 2021)
The article analyzes the expected return and portfolio risk. The development of a broad and efficient market, a statistical base, as well as rapid progress in the field of computing have led to the emergence of modern theory and practice of portfolio management. We have shown that it is based on the use of statistical and mathematical methods for selecting financial instruments in a portfolio, as well as on a number of new conceptual approaches.